Yellow Sugarcane Aphid, Sipha flava (Forbes) (Insecta: Heteroptera: Aphididae) - Gregg S. Nuessly (EDIS)
The yellow sugarcane aphid, Sipha flava (Forbes), was described from Illinois by Forbes in 1884. Originally referred to as the 'sorghum aphis' and placed in the genus Chaitophorus (Forbes 1884), it was later moved into the genus Sipha (Davis 1909). Sipha includes 12 species of grass feeders, at least four of which occur in North America north of Mexico. The yellow sugarcane aphid causes damage to sorghum, sugarcane and several species of pasture grass (Median-Gaud et al. 1965, Kindler and Dalrymple 1999). This document is EENY-354, one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date August 2005.